Efficiency assessment of hospital bed capacity in a regional oncology center: A observational retrospective study - O. V. Kudelina; K. A. Gamirova; M. Yu. Grishenko (Кубанский научный медицинский вестник, 2025)
Background. The efficiency of healthcare institutions directly affects the overall level of public health. Analyzing inpatient care performance provides an opportunity to assess the quality of medical services, identify existing organizational issues, and support the rational allocation of resources within the healthcare system. Objectives. To assess the dynamics of key indicators reflecting the efficiency in the use of beds allocated for oncology and radiology/radiotherapy care at the Tomsk Regional Oncology Center over the period from 2016 to 2023. Methods. A observational retrospective study was conducted using non-personalized data on patients treated at the oncology center from 2016 to 2023. Key indicators of hospital bed capacity were assessed for the oncology and radiology beds. The study sample and groups were formed using a continuous sampling method according to the inclusion criterion of having a malignant neoplasm. The data examined for the period 2016–2023 include the number of hospitalized patients, hospitalization rate per 1,000 population, bed availability per 10,000 population, bed occupancy, average length of stay, bed turnover, and bed downtime. These data were obtained from official federal statistical reporting forms. Descriptive statistical methods and mean value calculations were used for the statistical analysis of the obtained results. The analysis of the indicator “average length of hospital stay” included the calculation of the confidence interval, minimum and maximum values, median, and interquartile range for each care. A comparison was conducted with the corresponding (selective) indicators for the Tomsk Oblast. Results. Over the analyzed period, the number of patients treated in the day hospital at the Tomsk Regional Oncology Center tripled, whereas the number of patients hospitalized in inpatient (24-hour) departments increased by 83.8%. The analysis revealed that the availability of oncology beds for 24-hour inpatient care at the Tomsk Regional Oncology Center increased by more than one-third (41.7%). The value of the indicator for bed availability in the day hospital at the Center remained unchanged, whereas the availability of 24-hour inpatient beds in the Tomsk Region decreased by 16.1%. The overall efficiency of hospital bed capacity at the Tomsk Regional Oncology Center improved, primarily due to the more rational use of oncology beds in the 24-hour inpatient hospital setting. Conclusion. The proportion of hospitalizations in the day hospital at the Tomsk Regional Oncology Dispensary increased, which can be regarded as a positive trend toward shifting inpatient care to outpatient and day hospital settings. The average length of stay for oncology patients decreased due to the implementation of modern high-tech treatment methods and strengthened outpatient services